2000
DOI: 10.1111/j.1541-0064.2000.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain management in Canada: overview and prospects

Abstract: Flooding is an important natural process. It plays a vital role in the maintenance of floodplain and shoreline ecosystems. Yet, it also is a hazard, in that floods put human life and property at risk. Paradoxically, flooding is a hazard only because humans have chosen to occupy flood‐vulnerable areas, such as riverine floodplains and lake or coastal shorelines. Recent major floods in Canada are a reminder that vulnerability to floods remains high. Responses to the flooding “problem” have evolved in Canada from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Although evaluations found that the FDRP helped to identify high‐risk areas and made flood risk more transparent, the enforcement of floodplain regulations varied considerably across provinces, and elected politicians were unwilling to refuse requests for disaster assistance, so in 1999 the Government of Canada withdrew from the FDRP, opting not to renew the agreements with the provinces (de Loë, ; Kumar, Burton, & Etkin, ). Responding to the federal government's abrupt exit from the FDRP, experts warned that the progress that had been made towards a more comprehensive and risk‐based approach to flooding could be lost (de Loë, ; Shrubsole, ). One year later, an independent expert panel charted a path to revitalise FRM progress that would involve, among other things, updating flood maps and sharing responsibility with private sector actors such as banking institutions, real estate professionals, developers, and insurers (Kumar et al, ), but the plan was never implemented.…”
Section: Frm In Canadamentioning
confidence: 99%
“…Although evaluations found that the FDRP helped to identify high‐risk areas and made flood risk more transparent, the enforcement of floodplain regulations varied considerably across provinces, and elected politicians were unwilling to refuse requests for disaster assistance, so in 1999 the Government of Canada withdrew from the FDRP, opting not to renew the agreements with the provinces (de Loë, ; Kumar, Burton, & Etkin, ). Responding to the federal government's abrupt exit from the FDRP, experts warned that the progress that had been made towards a more comprehensive and risk‐based approach to flooding could be lost (de Loë, ; Shrubsole, ). One year later, an independent expert panel charted a path to revitalise FRM progress that would involve, among other things, updating flood maps and sharing responsibility with private sector actors such as banking institutions, real estate professionals, developers, and insurers (Kumar et al, ), but the plan was never implemented.…”
Section: Frm In Canadamentioning
confidence: 99%
“…Flood mapping in the Canadian federation is primarily the responsibility of the subnational provinces and territories, but the federal government has historically played a central role as well. For instance, the Flood Damage Reduction Program (FDRP) was an intergovernmental initiative that operated between 1975 and 1999, which sought to identify and map high-risk flood areas (de Loë 2000 ). This work resulted in 957 designated flood risk areas, most of which retain their designation today (Environment and Climate Change Canada 2013 ).…”
Section: Frm Policy Instrumentsmentioning
confidence: 99%
“…Unlike the USA and France, Canada didn't create a flood insurance system. With a change in government, the FDRP was phased out starting in the early 1990s and the last of the agreements expired in 2000 (de Loë, 2000).…”
Section: Legislative Framework For Regulatory Flood Maps In the Usa F...mentioning
confidence: 99%